The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/nbm.1940060202
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR spectroscopy of colon tumors and normal mucosal biopsies; elevated taurine levels and reduced polyethyleneglycol absorption in tumors may have diagnostic significance

Abstract: Twenty-three pairs of normal mucosa and colonic adenocarcinoma biopsy specimens have been examined in this pilot study by 1H NMR spectroscopy at 9.4 T to determine whether it was possible to find spectral malignancy markers. The 3.2 ppm (trimethylamine-containing compounds)/0.9 ppm (methyl of fatty acids) resonance intensity ratio in water suppressed spectra, proposed by other authors as a malignancy marker, results in our hands, using resonance areas, in partial overlap between tumor and mucosa values, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 25 publications
4
38
1
Order By: Relevance
“…Recently it has been reported that high taurine levels might be the expression of increased celluar proliferation and tumoral aggressiveness. 39 We suggest that medulloblastoma can be distinguished from ependymoma by this taurine peak (Fig. 2(e)).…”
Section: Neuroectodermal Tumor (Glioma)mentioning
confidence: 94%
“…Recently it has been reported that high taurine levels might be the expression of increased celluar proliferation and tumoral aggressiveness. 39 We suggest that medulloblastoma can be distinguished from ependymoma by this taurine peak (Fig. 2(e)).…”
Section: Neuroectodermal Tumor (Glioma)mentioning
confidence: 94%
“…Resonances were assigned by the spectral pattern in one-dimensional spectra of perchloric acid extracts, by two-dimensional COSY spectra on some samples, and by comparison with chemical shift values of pure compounds and literature values. 18,20,28,29 Peak-height and area analyses Selected spectral peak areas and peak-heights (see Fig. 1) were obtained using x-spec software (version 2.0.7; Bruker).…”
mentioning
confidence: 99%
“…[3][4][5] Significant increases in taurine, choline-containing compounds and lipid resonances were observed in malignant colon mucosa by one-dimensional 1 H NMR spectral data. 6 Altered metabolic profiles may provide potential biomarkers for detection, staging, prognostication, and treatment of colorectal cancer. 7 In this present study, we hypothesized that the metabolic profile in colorectal tissue would provide fingerprints of cancerous tissues that clearly differ from normal tissues.…”
Section: Introductionmentioning
confidence: 99%